1996
DOI: 10.1017/s1357729800015009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of space allowance during transport on the behavioural and physiological responses of lambs during and after transport

Abstract: There is limited information on the behavioural and physiological responses of sheep to the components of road transport. Behavioural observations and physiological measurements of ‘stress’, injury and dehydration were made on weaned lambs (35 kg) before, during and after either stationary confinement or transport for 22 h at four space allowances (0·22, 0·27, 0·31 and 0·41 m2 per sheep). Two groups were not loaded (a control group with access to food and water, and a group with no food and no water for 12 h).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 28 publications
5
55
0
11
Order By: Relevance
“…Growing animals may show increased levels of plasma albumin and/or total protein when transported for long periods of time (Cole et al, 1986;Tarrant et al, 1992;Cockram et al, 1996). However this increase could also result from dehydration (Cockram et al, 1996). Non-evaporative water loss was found by Cole et al (1986) to be higher in transported than in fasted steers, and faeces and urine excretion during transport accounted for about 003 of live weight, similar to the present results (003 to 0-04 of live weight).…”
Section: Effects Of Transportsupporting
confidence: 85%
See 2 more Smart Citations
“…Growing animals may show increased levels of plasma albumin and/or total protein when transported for long periods of time (Cole et al, 1986;Tarrant et al, 1992;Cockram et al, 1996). However this increase could also result from dehydration (Cockram et al, 1996). Non-evaporative water loss was found by Cole et al (1986) to be higher in transported than in fasted steers, and faeces and urine excretion during transport accounted for about 003 of live weight, similar to the present results (003 to 0-04 of live weight).…”
Section: Effects Of Transportsupporting
confidence: 85%
“…Motion, noise, vibration (Cockram et al, 1996) and space allowance (Tarrant et al, 1992) have been discussed as the most important stressors during transport. The onset of adaptive mechanisms could explain why plasma cortisol levels declined in the study of Cockram et al (1996) after several hours of transport. However, the 4-5 h of transport in experiment 1 of the present study would not appear sufficiently long to allow such a noticeable decrease in plasma cortisol.…”
Section: Effects Of Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not preclude the fact that this study can be a source of important reflection as some previous studies (Cockram et al, 1996). As mares were randomly assigned into groups, it is unlikely that the initial composition of the groups plays an important role in the differences observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…This might be due to the differences among the three stocking densities being insufficient to show physiological differences or those stocking densities affected to lambs in the same way. Cockram et al (1996) reported that weaned lambs transported for 12 h at four space allowances (0.22, 0.27, 0.31 and 0.41 m 2 /sheep) did not affect on plasma cortisol concentration and plasma CK activity.…”
Section: Discussionmentioning
confidence: 91%